Apparent digestibility of Ora-pro-nobis (Pereskia aculeata) leaf meal by Nile tilapia (Oreochromis niloticus) - Émerson José Alves Matos; Izabel Volkweis Zadinelo; Patricia da Silva Dias; Elisabeth Criscuolo Urbinati; Fábio Meurer (Pesquisa Agropecuária Gaúcha)
The objective of this study was to determine the apparent digestibility of ora-pro-nóbis leaf meal (OLM) in Nile tilapia diets, assessing the digestibility of crude protein (CP), amino acids (AA), gross energy (GE), ether extract (EE), and dry matter (DM). The indirect method with chromic oxide and feces collection by sedimentation was used. Two diets were formulated: a reference diet and a test diet, the latter containing 30.0 % OLM and 70.0 % of the reference diet. The apparent digestibility coefficients (ADC) of OLM were 30.01 % (DM), 40.60 % (GE), 76.86 % (EE), and 45.51 % (CP). Among the essential AA, tryptophan (98.00 %) and leucine (80.00 %) had the highest values, while threonine (25.00 %) and arginine (39.00 %) had the lowest. Despite its low protein and energy digestibility, OLM supplied significant amounts of essential amino acids that were absorbed by the fish. Thus, it can be used as a complementary ingredient in Nile tilapia diets, but not as the main protein or energy source.